Infection by CXCR4-Tropic Human Immunodeficiency Virus Type 1 Is Inhibited by the Cationic Cell-Penetrating Peptide Derived from HIV-1 Tat. (29th January 2012) - Keogan, Shawn; Passic, Shendra; Krebs, Fred C.
Abstract : Cell-penetrating peptides (CPP), which are short peptides that are capable of crossing the plasma membrane of a living cell, are under development as delivery vehicles for therapeutic agents that cannot themselves enter the cell. One well-studied CPP is the 10-amino acid peptide derived from the human immunodeficiency virus type 1 (HIV-1) Tat protein. In experiments to test the hypothesis that multiple cationic amino acids within Tat peptide confer antiviral activity against HIV-1, introduction of Tat peptide resulted in concentration-dependent inhibition of HIV-1 IIIB infection. Using Tat peptide variants containing arginine substitutions for two nonionic residues and two lysine residues, HIV-1 inhibition experiments demonstrated a direct relationship between cationic charge and antiviral potency. These studies of Tat peptide as an antiviral agent raise new questions about the role of Tat in HIV-1 replication and provide a starting point for the development of CPPs as novel HIV-1 inhibitors.